Transmitting and Circulating the Late Antique and Byzantine Worlds
1 online resource.
Keywords: Transmitting and Circulating the Late Antique and Byzantine Worlds seeks to be a crucial contribution to the history of medieval connectedness. Using one of the methodological tools associated with the global history movement, this volume aims to use connectedness to revitalise local and regional networks of exchange and movement. Its case studies collectively point caution toward assuming or asserting global-scale transmission of meaning or items unchanged, and show instead how meaning is locally produced and regionally formulated, and how this is no less dynamic than any global-level connectedness. These case studies by early career scholars range from the movement of cotton growing practices to the transmission of information within individual texts. Their wide scope, however, is nonetheless united by their preoccupation with transmission and circulation as categories of analysing or explaining movement and change in history. This volume hopes to be, therefore, a useful contribution to the growing field of a history of connectivity and connectedness. Contributors are Jovana Anđelković, Petér Bara, Mathew Barber, Julia Burdajewicz, Adele Curness, Carl Dixon, Alex MacFarlane, Anna Kelley, Matteo G. Randazzo, Katinka Sewing and Grace Stafford.